2017
DOI: 10.1002/hyp.11248
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of paired watersheds: Utility of moving sums in presence of externalities

Abstract: Historically, paired watershed studies have been used to quantify the hydrological effects of land use and management practices by concurrently monitoring 2 similar watersheds during calibration (pretreatment) and post‐treatment periods. This study characterizes seasonal water table and flow response to rainfall during the calibration period and tests a change detection technique of moving sums of recursive residuals (MOSUM) to select calibration periods for each control–treatment watershed pair when the regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(98 reference statements)
3
7
0
Order By: Relevance
“…With both the calibration periods spanning just two years, the authors attributed the observed differences in the flow relationships between these periods to modification of soil properties during the operational silvicultural activities during clear-cutting and logging. In another study at the same NC site, Ssegane et al (2017) found statistically significant pre-treatment relationships, consistent with those from the 1988-1990 pre-disturbance level, using only 762 days and 608 days (for two treatment watersheds) of stable calibration period from 2009 to 2012 period that included some disturbances in the watersheds. Bren and Lane (2014) found a rapid increase in quality of calibration relationship as the record length increases but with no increase after 3-year length for all temporal scales of flow.…”
Section: Tablesupporting
confidence: 57%
See 1 more Smart Citation
“…With both the calibration periods spanning just two years, the authors attributed the observed differences in the flow relationships between these periods to modification of soil properties during the operational silvicultural activities during clear-cutting and logging. In another study at the same NC site, Ssegane et al (2017) found statistically significant pre-treatment relationships, consistent with those from the 1988-1990 pre-disturbance level, using only 762 days and 608 days (for two treatment watersheds) of stable calibration period from 2009 to 2012 period that included some disturbances in the watersheds. Bren and Lane (2014) found a rapid increase in quality of calibration relationship as the record length increases but with no increase after 3-year length for all temporal scales of flow.…”
Section: Tablesupporting
confidence: 57%
“…Ordinary least squares regression (OLS) was used to develop a calibration equation between the control and treatment watersheds and its significance test (Warton, Wright, Falster, & Westoby, 2006). However, since Durbin-Watson test (SAS, 2006) showed a positive autocorrelation of the monthly runoff on both the watersheds, we compared for differences between regression relationships using OLS versus using a resampling technique that accounts for serial correlation in time series and geometric mean (GM) regression, following (Ssegane et al, 2017), using the ts andlmodle2 R-statistical package (R Development Core Team, 2015). In this approach, the original data were resampled in pre-determined blocks 1000 times to estimate regression coefficients.…”
Section: Data and Statistical Analysesmentioning
confidence: 99%
“…A large pump installed at the main roadside ditch (downstream of all weir outlets) minimized weir submergence during large storm events [9]. Other details of hydro-meteorological measurements were documented [12].…”
Section: Field Measurement Of Precipitation and Flowmentioning
confidence: 99%
“…Because the calibration Eq. 6 obtained by a bootstrap regression (Ssegane et al, 2017; that potentially reduces the effects of autocorrelation in daily values) was significant, we chose it to correct the bias in daily solar radiation data (Mj m -2 d -1 ) from the downloaded hourly data for all the stations.…”
Section: Solar Radiation (R S )mentioning
confidence: 99%